Evaluasi Standar Pelayanan Kefarmasian Di Apotek Lombok Tengah Berdasarkan Kemenkes No.1027/MENKES/SK/IX/2004 NTB - Ningrum, Dwi Monika; Zainudin, Ahmad -; Yuliana, Depi; Bayani, Faizul (Jurnal Kesehatan Qamarul Huda, 2018)
Pharmacists in carrying out their duties at the Pharmacy need to comply with Kepmenkes No.1027 / Menkes / SK / IX / 2004, concerning Pharmaceutical Service Standards at the Pharmacy. These standards are structured as guidelines for the practice of pharmacists in carrying out their work, so that the public is protected from unprofessional services and minimizes the occurrence of medication errors. This study aims to determine the standard application of pharmaceutical services at the Pharmacy. This study was designed in a non-experimental manner, in which the results were displayed descriptively. Sampling process was using the Slovin formula, therefore from 67 pharmacies that existed in this particular area were obtained sample of 38 pharmacies in Central Lombok. Data collection was based on the results of interviews with pharmacists and direct observation to determine compliance with the standard technical implementation of pharmaceutical services at the pharmacy (SK No.1027 / Menkes / SK / IX / 2004). Scoring was done by summing the value of each indicator in each Pharmacy which includes human resources, services and evaluation of service quality. The results of the assessment indicate that there is 1 Pharmacy (2.33%) in the good category, 13 Pharmacies (30.23%) in the sufficient category and 29 Pharmacies (67.44%) in the less category.